The effect of catalyst composition for palm oil waste gasification: thermal gravimetric analysis - Nur Suhada, Amran (2014)
Fossil fuels demand is increasing rapidly because of the growth of population and industrialization. However, the conventional energy source is depleted. Biomass is abundant but inefficiently utilized. Gasification of biomass is the one of the alternative ways to encounter this problem. This research aims to study the effect of catalyst composition for palm oil waste gasification and to synthesis and characterize the catalyst. Empty Fruit Bunch (EFB), Palm Oil Fiber (POF) and Palm Oil Shell (POS) were initially analyzed by using a thermogravimetric analyzer (TGA). It is found that EFB contain more volatile matter in comparison to POF and POS. The high content of volatile matter makes EFB highly volatile, reactive and very suitable for gas fuel production. It can also be deduced that EFB might produce more hydrogen than POF and POS. The catalysts were prepared via a wet impregnation method. The nickel alumina catalyst with various weight percent of the promoter, Ce or Ca, were synthesised and tested with a sample consisted of 1:1 weight percent of catalyst to biomass in the Thermo gravimetric Analysis (TGA). The influence of Ce loading on the Ni/Ce/Al203 , the different promoters, (Ce or Ca), loading in the Ni/Al203 and the different ratio of Nickel loading in the Ni/Ce/Al203 were investigated in the gasification of EFB in the Thermo gravimetric Analysis (TGA). Based on the result, Ce show better performance compared to Ca. The result shows the optimum Ce loading was 10 wt% and Ni loading of 5wt%. The 5Ni/1OCe/Al203 catalyst was found to be the best catalyst for the palm oil waste gasification.